Elevated ischemic stroke risk among women living with HIV infection. (2nd January 2018) - Chow, Felicia C.; Regan, Susan; Zanni, Markella V.; Looby, Sara E.; Bushnell, Cheryl D.; Meigs, James B.; Grinspoon, Steven K.; Feske, Steve K.; Triant, Virginia A.
Abstract : Objective: To determine if the greater risk of ischemic stroke observed in women living with HIV infection (WLWH) compared with HIV-uninfected women persists after accounting for both traditional and sex-specific stroke risk factors. Methods: We performed an observational cohort study of WLWH ( n  = 1214) and demographics-matched HIV-uninfected women ( n  = 12 041) seen between 1996 and 2011 at two tertiary care hospitals in Boston. We used Cox proportional hazards regression analyses to model time to ischemic stroke, adjusting first for demographics and traditional stroke risk factors and then for sex-specific stroke risk factors, including menopause and estrogen use. We also constructed demographics-adjusted Cox models to identify HIV-related risk factors associated with ischemic stroke among WLWH. Results: The incidence of ischemic stroke was higher among WLWH compared with HIV-uninfected women [incidence rate ratio 2.39, 95% confidence interval (CI) 1.62–3.43]. After adjusting for demographics and traditional stroke risk factors, HIV infection was associated with almost twice the risk of ischemic stroke (hazard ratio 1.93, 95% CI 1.31–2.85). The association of HIV with ischemic stroke persisted after inclusion of sex-specific stroke risk factors in the model (hazard ratio 1.89, 95% CI 1.28–2.81). Among WLWH, longer duration of antiretroviral therapy was associated with lower ischemic stroke risk (hazard ratio 0.86 per year, 95% CI 0.76–0.96). Conclusion: The increased risk of ischemic stroke among WLWH compared with HIV-uninfected women persisted after adjusting for both traditional and sex-specific stroke risk factors. Further investigation into the mechanisms of elevated stroke risk among WLWH, including immunologic factors, will be key for developing targeted preventive strategies for this at-risk population. Abstract : Supplemental Digital Content is available in the text